A new sociality for a solidarity-based society : the altruistic relationships - Mangone, Emiliana (Universidad Pedagógica y Tecnológica de Colombia, 2022)
One should not imagine that the social sciences discovered altruism only when Comte coined the term – understood as a powerful impulse to the intellectual and moral development of humanity towards which the latter must tend as its future state. Indeed, since ancient times, scholars have attempted to explain (cause-effect) and understand (sense and meaning) why in certain situations some men behave positively towards others (altruistic behaviour) while similar situations the same men behave differently. While not claiming to be exhaustive either theoretically or temporally, we will present an overview on the theme through the ideas of some sociologists (Comte, Durkheim, Mauss, and Sorokin) who have contributed the most to shed light to this object of study. We will argue that the rediscovery of altruism can be seen as a new form of sociality between Ego/Alter for a solidarity-based society.